(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The development of a new strategy for industrial development of the Kyrgyz Republic until 2030 is of particular importance against the backdrop of the global transformation of economies, sustainability challenges and the need for structural diversification. The purpose of the article is not only to analyze the current problems and potential of the industrial sector, but also to formulate a reasoned position in support of the development and implementation of a new industrial strategy for Kyrgyzstan based on international practices and modern challenges. The authors seek to motivate government bodies, the academic and expert community to actively participate in this process. The article examines the lessons of previous strategies, analyzes the goals and structure of the new Strategy being developed by SRIEk in cooperation with UNIDO and international partners. The article presents current international approaches to sustainable industrialization. It concludes that it is necessary to move from declarative goals to clearly measurable development mechanisms.